The effect of Pilates practice on balance in elderly: a systematic review - Goedert, Araceli (2018)
The aging is accompanied by a gradual decline in balance and increases risk of falls. Pilates has been used for balance training. e purpose of this research was to systematize studies regarding the effects of Pilates exercise interventions on static and dynamic balance of elderly people. A survey was conducted in three indexed databases: Medline/Pubmed, Scopus and Science Direct, using the descriptors “balance” or “equilibrium” with the term “Pilates”. Fifteen articles were selected and used in this systematic review. Based on the results, we observed that the practice of Pilates with a minimum frequency of two sessions per week for an hour lasting for a period of at least five weeks or three times per week for 12 sessions or more showed improvement on static and dynamic balance of elderly.